Un pays à l’image d’une jambe humaine : anatomie de l’imaginaire géographique et paysager italien - Justine Balibar (Projets de Paysage)
Advertising images and images promoting tourism have accustomed us to associate Italy with the image of a boot. This highly contemporary image is actually rooted in a much older image, which was just as popular during the Renaissance and which represented Italy as a human leg. This image first appeared in a geography book by Leandro Alberti dating from 1551, entitled Descrittione di tutta Italia, which was very successful during the Renaissance. Behind the iconic function of popularisation inherent in all imagery, this image has a deeper significance in that it makes a territory perceptible in its entirety by giving it a form of geographical unity. Embodied in this image is the problem of the unity of Italy; not of the country’s political unity but of its unity geographically and as a landscape. In more precise terms, it poses the problem of understanding the Italian territory as a unified set of different regional landscapes.